2002
DOI: 10.1002/cncr.10728
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of grading and staging systems using MIB‐1 score in adult patients with soft tissue sarcoma of the extremities and trunk

Abstract: BACKGROUND The predictive value of histologic grading and staging systems for overall survival in different types of adult soft tissue sarcoma of the extremities and trunk is unclear. METHODS Histologic slides from 193 patients with primary tumors were reviewed for diagnosis, and Ki‐67 (MIB‐1) immunostaining was performed for grading in all patients. Univariate and multivariate analyses were conducted to analyze the results from patients with soft tissue sarcomas as a group and among the six main histologic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
57
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 16 publications
5
57
2
Order By: Relevance
“…A Ki-67 LI was correlated with the poor prognosis of patients with several malignancies (28,34,43). Ki-67 has been used as a common and valuable prognostic marker in STSs (8,9,44,45). We also showed that MCM7 and Geminin LIs are positively correlated with Ki-67 LIs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A Ki-67 LI was correlated with the poor prognosis of patients with several malignancies (28,34,43). Ki-67 has been used as a common and valuable prognostic marker in STSs (8,9,44,45). We also showed that MCM7 and Geminin LIs are positively correlated with Ki-67 LIs.…”
Section: Discussionsupporting
confidence: 52%
“…Ki-67 was present throughout the complete cell cycle, except for the early G1 phase, which is associated with poor prognosis of the disease (43)(44)(45). A Ki-67 LI was correlated with the poor prognosis of patients with several malignancies (28,34,43).…”
Section: Discussionmentioning
confidence: 99%
“…21 Nonetheless, it is not simple to conduct prospective and randomized studies, because of the rarity of each entity. In this perspective, a retrospective analysis represents a useful tool with which to define prognostic factors and the best treatment strategy, accepting the drawbacks of this kind of study design.…”
Section: Discussionmentioning
confidence: 99%
“…Interobserver variability in application of tumor grading criteria can be virtually eliminated by use of the reproducible FNCLCC grading scheme, which has prognostic value. 22 Errors in the histological subtyping of primary pulmonary and mediastinal synovial sarcoma can occur when entrapped pneumocytes are misinterpreted as the epithelial component of biphasic tumors. Entrapped pneumocytes are cytologically benign, are typically arranged in small clusters and/ or well-formed gland-like structures at the periphery of the tumor (Figure 3e), and are immunoreactive with thyroid transcription factor-1 (Figure 3f).…”
Section: Discussionmentioning
confidence: 99%